2018
DOI: 10.3390/ma11020218
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Properties of O-Doped Pure and Sulfur Vacancy-Defect Monolayer WS2: A First-Principles Study

Abstract: Based on the density functional theory (DFT), the electronic properties of O-doped pure and sulfur vacancy-defect monolayer WS2 are investigated by using the first-principles method. For the O-doped pure monolayer WS2, four sizes (2 × 2 × 1, 3 × 3 × 1, 4 × 4 × 1 and 5 × 5 × 1) of supercell are discussed to probe the effects of O doping concentration on the electronic structure. For the 2 × 2 × 1 supercell with 12.5% O doping concentration, the band gap of O-doped pure WS2 is reduced by 8.9% displaying an indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 27 publications
(28 reference statements)
3
15
1
Order By: Relevance
“…Similarly, Wang et al [210] also studied the influence of O doping on WS 2 using a theoretical calculation. The calculation results suggested that the relatively high doping concentration would reduce the band gap, while the conclusion was opposite at a relatively low concentration.…”
Section: Theoretical Calculations Of Wsmentioning
confidence: 99%
“…Similarly, Wang et al [210] also studied the influence of O doping on WS 2 using a theoretical calculation. The calculation results suggested that the relatively high doping concentration would reduce the band gap, while the conclusion was opposite at a relatively low concentration.…”
Section: Theoretical Calculations Of Wsmentioning
confidence: 99%
“…It was consistent with the Hund's rules, that electrons always take precedence of different orbits and have the same spin direction occupying the equivalent orbital. Owing to quantum size and surface effects, two-dimensional (2D) materials may present extensive novel physical and chemical properties, when downsizing from three dimensions to two dimensions or one dimension [20][21][22][23][44][45][46][47]. To further investigate the interrelationship between thickness and magnetism in CrSi2, we also calculated magnetic moment of unit cell of 2D multilayer nanosheets with different layers.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…As the layers increase, the decrease of magnetic moments occurs in CrSi 2 nanosheets. Considering weak van der Waals force and strong chemical bonds between layers, quantum size [20][21][22][23]46] and surface effects [44] occur when downsizing from bilayers to monolayer in CrSi 2 nanosheets. We deduced that the band energy between layers, as well as quantum size and surface effects play an important role in magnetism of materials.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations